ANALISIS RANTAI PASOK SAYURAN PAKCOY DENGAN SISTEM BUDIDAYA RAMAH LINGKUNGAN: STUDI KASUS TANI KOTA, KOTA BANDUNG - Pitania Naelil Zakiyah; Tuti Karyani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The vegetables are part of basic needs. Because, a healthy lifestyle growing up prompting citizens to consume more vegetables especially organic vegetables, because it’s safer to consume. Tani Kota is one of the supplier of vegetables in Bandung. However, there are obstacles in fulfilling consumer demand. This research purpose to identify the supply chain and farm income of Pakcoy. The analysis tool is development supply chain of agricultural product methods by APO and farm analysis. Based on the research result, there are cause of problem in supply chain is unable to fulfilling consumer demand because the planting schedule isn’t effective and vegetables not ready to harvest. The result of farm analysis of organic pakcoy is R/C > 1,71, so that it can be said pakcoy farming profitable to be cultivated.